Milk Transmission of Mammalian Retroviruses - Kemeter, Laura; Birzer, Alexandra; Heym, Stefanie; Thoma-Kreß, Andrea (Microorganisms, 2023)
The transmission of viruses from one host to another typically occurs through horizontal or vertical pathways. The horizontal pathways include transmission amongst individuals, usually through bodily fluids or excretions, while vertical transmission transpires from mother to their offspring, either during pregnancy, childbirth, or breastfeeding. While there are more than 200 human pathogenic viruses to date, only a small number of them are known to be transmitted via breast milk, including cytomegalovirus (CMV), human immunodeficiency virus type 1 (HIV-1), and human T cell lymphotropic virus type 1 (HTLV-1), the latter two belonging to the family Retroviridae. Breast milk transmission is a common characteristic among mammalian retroviruses, but there is a lack of reports summarizing our knowledge regarding this route of transmission of mammalian retroviruses. Here, we provide an overview of the transmission of mammalian exogenous retroviruses with a focus on Orthoretrovirinae, and we highlight whether they have been described or suspected to be transmitted through breast milk, covering various species. We also elaborate on the production and composition of breast milk and discuss potential entry sites of exogenous mammalian retroviruses during oral transmission.
CRIS-Team Scopus Importer:2023-08-11
Keywords: breast milk; breastfeeding; human immunodeficiency virus (HIV); human T cell lymphotropic virus type 1 (HTLV-1); mammalian retrovirus; oral route; retrovirus; salivary glands; tonsils; virus transmission